Krukenberg tumor - Nitesh Thakur,; Suman Thakur,; Kushla Pathania,; Rama Thakur, (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Krukenberg tumor is a rare form of metastatic ovarian cancer which accounts for less than 2% of all ovarian tumor. Krukenberg tumor mostly occurs after the age of 40 years and is rarely found in younger age group. It usually presents with bilateral involvement of ovaries. It presents when the primary is already advanced. Here we are presenting a rare case of Krukenberg tumor in a 22 years old female with primary from stomach.